2009
DOI: 10.1063/1.3097903
|View full text |Cite
|
Sign up to set email alerts
|

Shot to shot variation in perveance of the explosive emission electron beam diode

Abstract: The shot to shot variation in perveance of a planar diode with explosive emission graphite cathode in a range of accelerating gaps 3–12 mm is investigated experimentally. The typical electron beam parameters were 200 kV, 12 kA, 100 ns, with a few hundreds of A/cm2 current density. The diode perveance remains less than the Child–Langmuir value, indicating that only a fraction of the cathode take part in the emission process. A simple statistical analysis of the diode perveance shows that the shot to shot variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…But in the case of a planar diode the initial emission area increases with the accelerating gap. 11 In our previous experiments with 50 mm diameter planar graphite cathode and 1.3 cm AK gap the maximum diode voltage obtained was only 185 kV with a very high current of 43.5 kA. 14 A very fast gap closer has been observed in this planar diode experiment.…”
Section: Experimental Results and Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…But in the case of a planar diode the initial emission area increases with the accelerating gap. 11 In our previous experiments with 50 mm diameter planar graphite cathode and 1.3 cm AK gap the maximum diode voltage obtained was only 185 kV with a very high current of 43.5 kA. 14 A very fast gap closer has been observed in this planar diode experiment.…”
Section: Experimental Results and Analysismentioning
confidence: 62%
“…Also it may so happen that the full cathode fails to participate in the emission process leading to a current less than that predicted by the space-charge law. 11 Therefore, it is very difficult to predict the diode current unless we know the cathode and anode plasma expansion velocity and the effective emission area. Time and space resolved optical measurements are to be carried out to measure the plasma velocity and the effective emission area.…”
Section: Introductionmentioning
confidence: 99%
“…The results of experimental investigations on shot-to-shot variation in the perveance of a planar electron diode with a graphite explosive-emission cathode were reported by Roy et al 6 It was shown that the perveance shot-to-shot variation increases from 24% at t = 50 ns, and up to 60% at t = 90 ns. In this case the variation was explained by variations in the effective emission area of the cathode and anodecathode (A-K) gap spacing due to the expending plasma, where the expansion was both radial and axial.…”
Section: Introductionmentioning
confidence: 77%
“…During the last decades, several statistical methods have been applied to electromagnetic [13]- [15], mechanical problems [16], and Vircator studies [17]- [20]. From crude Monte Carlo (MC) [21], [22] (known as a brute force technique) to Polynomial Chaos [23], [24], it has been shown how the confidence level could be assessed when dealing with random variables [25].…”
Section: Introductionmentioning
confidence: 99%